PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Telkom Witel Semarang) - Chandra Pralampita, 14.05.51.0277; Rozak, Hasan Abdul (Students' Journal of Economic and Management, 2018)
This study aims to examine and analyze the influence of Leadership Style, Motivation and Work Discipline on employee performance. The analytical tool used is multiple regression. For testing hypotheses, it is used t test. Data collection are through questionnaires with measurements using a Likert scale of 5 (five) alternative answers. The object of research is employees of PT. Telkom Witel Semarang. The number of samples in this study was 115 respondents. The sampling technique uses a simple random sampling. The results showed that (1) Leadership Style has a positive and significant effect on employee performance (2) Motivation has no effect on employee performance, (3) Work Discipline has a positive and significant effect on employee performance. Keywords: Leadership Style, Motivation, Work Discipline, Employee Performance